Anti-Symmetric Wing Transmitter for Angular Misalignment Insensitive Wireless Power Transfer to Biomedical Implants - Hoang Le-Huu; Chulhun Seo (IEEE Access, 2023)
This paper presents an anti-symmetric wing transmitter (ASW-Tx) for angular misalignment insensitive WPT to biomedical implants. Symmetrical field distribution on two orthogonal planes of $Oxz$ and $Oyz$ are analyzed theoretically to obtain stable power transfer efficiency (PTE) by rotating Rx around the $Oz$ axis. Moreover, toroidal magnetic fluxes are generated by ASW to adapt with different Rx’s tilted angles on $Ox$ and $Oy$ axes. An impedance matching network (IMN) is proposed and implemented to match ASW-Tx’s impedance to source impedance. An implantable Rx is employed to verify the ASW-Tx’s performance. Experimental measurements are carried out with selected Rx’s tilted angles (vary from $0^{o}$ to $90^{o}$ around $Ox$ , $Oy$ , and $Oz$ axis) to validate the effectiveness of proposed ASW-Tx’s. Verification results show that a stable efficiency variation was achieved with a maximum fluctuation of 4 dB by rotating Rx tilted angles. Moreover, the ASW-Tx can supply power effectively with a transmission efficiency of up to -18.4 dB to an implantation depth of 15 mm.